The wishing game : a novel - Shaffer, Meg (Ballantine Group, 2023)
"A retired bestselling author hosts a one-of-a-kind competition, with high risks and high rewards-giving the winner a chance to change lives. Lucy Hart has come a long way since feeling the cold neglect of her parents, whose attention always centered around her chronically ill sister's needs. Now a twenty-six-year-old teacher's aide, Lucy is able to share her love of books with bright, young students, and one in particular, a seven-year-old orphan named Christopher, has her yearning for a family of her own. The Clock Island books were Lucy's passion and refuge as a child, and now she shares them with Christopher, who's become as big of a fan as she ever was. No matter how badly Lucy wants him in her life, even the idea of adopting him seems out of reach without proper funds and stability. Then a blue envelope arrives at her school, inviting Lucy to compete for the one and only copy of Jack Masterson's final novel in the iconic Clock Island series. No one has seen or heard from Jack Masterson in years, but now four diehard Clock Island fans have received the invitation of a lifetime to stay on his private island and compete for the final installment, and unpublished manuscript, of the well-loved series. For Lucy, a chance to read the last-ever Clock Island book is a prize worth playing for, but the possibility of winning and securing a better future for her and Christopher means everything. But first, she must contend with opportunists, cheaters, and, perhaps most distressingly, Jack's illustrator and companion on the island, Hugo Reese, whom Lucy has admired since first reading the books as a girl. All the while, the master of ceremonies, the prolific author himself, has his own secrets to keep-and a larger plan in the works that will change everything for all of them"--